The Influence of Leadership on Room Attendant Performance at Rocky Plaza Hotel Padang - Aulia Ramadhani; Kurnia Illahi Manvi; Feri Ferdian; Yuke Permata Lisna (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Although leadership in the hospitality industry has received considerable scholarly attention, studies specifically examining its effect on room attendant performance remain limited. This study aims to analyze the influence of leadership on the performance of room attendants at Rocky Plaza Hotel Padang. A quantitative approach with a cross-sectional survey design was employed, involving 83 respondents selected through saturated sampling. Data were collected using questionnaires and analyzed using descriptive statistics, prerequisite tests, Spearman correlation, and simple linear regression with SPSS. The findings indicate that both leadership and room attendant performance were categorized as very good. The analysis further shows a positive and significant influence of leadership on performance, with a correlation coefficient of 0.503 and a contribution of 16.3%. These findings confirm that improving leadership quality can support better employee performance, although the magnitude of the effect is in the moderate category. The study contributes to hospitality management literature by providing empirical evidence on the role of leadership in shaping room attendant performance. Practically, the findings imply that hotel management should strengthen inspirational leadership practices and empower employees to improve work quality, autonomy, and service performance.